INNOVATIVE METHODS IN READING: HOW MOTIVATION SHAPES UNDERSTANDING - Mirzamakhmudova Iroda (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article explores the essential role of motivation in reading comprehension. Reading is not merely the act of recognizing words but a higher-order cognitive process involving decoding, understanding, and reasoning. The study examines different types of reading, factors that decrease motivation, and effective solutions to inspire and sustain reading habits. It also highlights practical methods to enhance the reading experience and improve comprehension through motivational and cognitive techniques.